Exosomes and the Prion Protein: More than One Truth - Hartmann, Alexander; Muth, Christiane; Dabrowski, Oliver; Krasemann, Susanne; Glatzel, Markus (Frontiers in Neuroscience, 2017)
Exosomes are involved in the progression of neurodegenerative diseases. The cellular prion protein (PrPC) is highly expressed on exosomes. In neurodegenerative diseases, PrPC has at least two functions: It is the substrate for the generation of pathological prion protein (PrPSc), a key player in the pathophysiology of prion diseases. On the other hand, it binds neurotoxic amyloid-beta (Aß) oligomers, which are associated with initiation and progression of Alzheimer’s disease (AD). This has direct consequences for the role of exosomal expressed PrPC. In prion diseases, exosomal PrP leads to efficient dissemination of pathological prion protein, thus promoting spreading and transmission of the disease. In AD, exosomal PrPC can bind and detoxify Aß oligomers thus acting protective. In both scenarios, assessment of the state of PrPC on exosomes derived from blood or cerebrospinal fluid (CSF) may be useful for diagnostic workup of these diseases. This review sums up current knowledge of the role of exosomal PrPC on different aspects of Alzheimer’s and prion disease.